How are multilingual communities of practice being considered in language assessment? A language ecology approach. - Arias, Angel; Schissel, Jamie L. (Journal of Multilingual Theories & Practices, 2021)
The article presents the discussion on developing innovations in multilingual assessment research. Topics include informing further scholarship in multilingual assessment and validation frameworks for researchers, policy-makers, and practitioners; and trained in assessment-centred communities such as educational measurement, psychometrics, measurement and quantitative psychology.